Tracheostomy in infants with severe bronchopulmonary dysplasia: A review - Akangire, Gangaram; Manimtim, Winston (Frontiers in Pediatrics, 2023)
In recent years, with increased survival of infants with severe bronchopulmonary dysplasia (BPD), long term ventilation due to severe BPD has increased and become the most common indication for tracheostomy in infants less than one year of age. Evidence shows that tracheostomy in severe BPD may improve short- and long-term respiratory and neurodevelopmental outcomes. However, there is significant variation among centers in the indication, timing, intensive care management, and follow-up care after hospital discharge of infants with severe BPD who received tracheostomy for chronic ventilation. The timing of liberation from the ventilator, odds of decannulation, rate of rehospitalization, growth, and neurodevelopment are all clinically important outcomes that can guide both clinicians and parents to make a well-informed decision when choosing tracheostomy and long-term assisted ventilation for infants with severe BPD. This review summarizes the current literature regarding the indications and timing of tracheostomy placement in infants with severe BPD, highlights center variability in both intensive care and outpatient follow-up settings, and describes outcomes of infants with severe BPD who received tracheostomy.